Analisis Kebutuhan Pengembangan Media Video Pembelajaran Tata Boga bagi Murid Tunarungu - Abdul Rahman; Siti Masitoh; Andi Mariono (Ideas Publishing, 2022)
This research was conducted to identify the need for instructional media before the development of cooking video media. The results of this needs analysis will be the basis for making video materials for deaf students. Needs analysis needs to be done as part of the pre-development stage of the research and development (R&D) process, using research subjects of as many as 13 classroom teachers, as well as researchers conducting observations and collecting data through a google form questionnaire distributed via Whatsapp. Based on the research findings that to involve deaf students in the culinary learning process and generate a desire to learn, innovative learning media are needed so that deaf students can achieve maximum learning goals and improve learning outcomes.